The Correlation of Plant-Based Diet with COVID-19 Severity and Symptoms among Individuals Recovered from the Disease - Fatemeh Almasi; Mohammad Nemati; Narges Izadi; Mohammad Mehdi Haghighat_Lari; Fateme Barforoush; Armin Ebrahimzadeh; Alireza Milajerdi (International Journal of Nutrition Sciences)
Background: COVID-19 is an infectious disease that has spread all over the world and has endangered health care system. Several studies have shown an association between Plant-based diets and the health benefits. This study aimed to investigate the association between Plant-based Diet Index (PDI) and severity and symptoms of COVID-19.Methods: In a cross-sectional study, 684 patients recovered from COVID-19 were included. Dietary intakes of subjects were assessed using a validated 168-item food frequency questionnaire and PDI, healthful PDI (hPDI) and unhealthful PDI (uPDI). The outcomes such as severity of disease, symptoms and levels of inflammatory biomarkers were assessed through telephone interviews with the participants.Results: After adjusting for several confounders, participants at the highest quartile of PDI showed lower risks for hypoxia, duration of disease and hospitalization and a lower level of ESR. PDI score was negatively associated with risk of COVID-19 symptoms including fever, chill, weakness, myalgia, chest pain, headache, dizziness, sore throat, diarrhea, nausea, vomiting and anorexia. A greater hPDI score was associated with reduced risk of sever COVID-19, hypoxia, need to respiratory support, lower duration of disease, recovery, lower level of CRP and ESR. A higher uPDI score was associated with greater risk of severe COVID-19, need to respiratory support, duration of disease, higher level of CRP and ESR.Conclusion: We found that higher PDI was associated with lower risk of COVID-19 outcomes. Also, higher hPDI and lower uPDI scores were associated with reduced risk of sever COVID-19.